Case Report: Giant mesenteric hemolymphangioma enveloping the ileum - Yu, Guan-Ying; Liu, Qi; Yan, Jing-Du; Shi, Xiao-Yan; Yang, Qing-Qing; Wang, Bao-xuan; Li, Cheng-Zhen; Guo, Pei-ming; Jiao, Jie; Zhang, Hou-Jun; Shi, Jing-Bo; Zhang, Lei (Frontiers in Oncology, 2025)
Hemolymphangiomas are rare, benign tumors arising from lymphatic and vascular tissues, most commonly found in subcutaneous and soft tissues, with their occurrence in the gastrointestinal tract, especially the mesentery, being uncommon. Due to their heterogeneous imaging features, these tumors are often misdiagnosed as malignancies, particularly when located in the abdominal cavity. We report a case of a 16-year-old male presenting with abdominal pain, vomiting, and diarrhea for 7 days. Imaging revealed a large, heterogeneous mass in the right lower abdomen, initially suspected to be a malignant mesenteric tumor. An ultrasound-guided biopsy and immunohistochemistry confirmed the diagnosis of hemolymphangioma. The patient underwent a combined laparoscopic and open surgical approach, including en bloc resection of the tumor, along with a segment of the ileum and surrounding mesentery. Histopathological examination verified the presence of lymphatic and vascular components consistent with hemolymphangioma. The patient recovered uneventfully and showed no recurrence at a 3-month follow-up. Hemolymphangiomas, although rare, should be considered in the differential diagnosis of mesenteric tumors.